"He Iwi tahi tatou": Aotearoa and the legacy of state-sponsored national narrative. (17th July 2020) - Kinnear, Susan Lilico
Abstract : Purpose: The purpose of this paper is to discuss the internal historical forces that shaped national identity in New Zealand and how state-sponsored ideographs and cultural narratives, played out in nation branding, government–public relations activity, film and the literature, contributed to the rise of present days' racism and hostility towards non-Pakeha constructions of New Zealand's self-imagining. Design/methodology/approach: The paper takes a cultural materialist approach, coupled with postcolonial perspectives, to build an empirical framework to analyse specific historical texts and artefacts that were supported and promoted by the New Zealand Government at the point of decolonisation. Traditional constructions of cultural nationalism, communicated through state-sponsored advertising, public information films and national literature, are challenged and re-evaluated in the context of race, gender and socio-economic status. Findings: A total of three major groupings or themes were identified: crew, core and counterdiscourse cultures that each projected a different construction of New Zealand's national identity. These interwoven themes produced a wider interpretation of identity than traditional cultural nationalist constructions allowed, still contributing to exclusionary formations of identity that alienated non-Pakeha New Zealanders and encouraged racism and intolerance. Research limitations/implications: The research study is empirical in nature and belongs to a larger project looking at a range of Pakeha constructions of identity. The article itself does not therefore fully consider Maori constructions of New Zealand's identity. Originality/value: The focus on combining cultural materialism, postcolonial approaches to analysis and counterdiscourse in order to analyse historical national narrative provides a unique perspective on the forces that contribute to racism and intolerance in New Zealand's society. The framework developed can be used to evaluate the historical government communications activity and to better understand how nation branding leads to the exclusion of minority communities.